The effect of thickness on out-of-plane constraint in terms of the T-stress - Yu.G. Matvienko (Fracture and Structural Integrity)
The plastic zone is theoretically and numerically analyzed for various combinations of the nonsingular terms xx T to zz T ratios in connection with specimen thickness under mode I loading. The plastic zone size distribution is based on the Mises yield criterion for mode I conditions and mapped in the specimen thickness direction. It is shown that the plastic zone size is affected by the zz T -stress, i.e. there is strong effect of out-of-plane constraint (thickness) on crack tip plastic zones. In addition, to study the effect of thickness and loading mode mixity (mode I and II) of the specimen on the singular (KI, KII) and the non-singular ( xx T , zz T ) terms along the 3D crack front, three-dimensional stress fields are analyzed by means of finite element analysis. The strong effect of thickness and mixed mode loading conditions on the zz T -stress is observed. At the same time, there is not the effect of thickness on the nonsingular xx T -stress at the same loading conditions.